Towards the Curtailment of the Baby Factory Syndrome in Nigeria - Owolabi, Elizabeth Folake (NIU Journal of Humanities, 2017)
This paper examines the â€œBaby Factoryâ€ Syndrome in Nigeria, a country already plagued by several cases of human rights violations especially in the area of human trafficking. It evaluates the nature and modus operandi of the baby factories operative in Nigeria. The paper examines the motivations and causes of the illicit trade in children, the fate of children from baby factories and the different forms of abuse that children born in the baby factories suffer. An analysis of the legal implication of operating a baby factory in Nigeria is carried out and the paper makes several far reaching recommendations that include reworking the legal framework of child-related issues, alleviating poverty and orientating the masses as ways through which the operation of baby factories in Nigeria can be drastically reduced and eventually eliminated. Keywords : Baby Factories, Child Abuse, Child Right, Human Trafficking, Nigeria.